Use of apps to promote childhood vaccination: systematic review - de Cock, C; Van Velthoven, M; Milne-Ives, M; Mooney, M; Meinert, E (JMIR Publications, 2020)
Background: Vaccination is a critical step to reducing child mortality; however, vaccination rates have declined in many countries in recent years. This decrease has been associated with an increase in outbreaks of vaccine-preventable diseases. The potential for leveraging mobile platforms to promote vaccination coverage has been investigated in the development of numerous mobile apps. Whilst many are available for public use, there is little robust evaluation of these applications. Objective: This systematic review aims to assess the effectiveness of applications supporting childhood vaccinations in improving vaccination uptake, knowledge and decision-making as well as the usability and user perceptions of these applications. Methods: PubMed, Medline, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), ClinicalTrials.gov and ERIC databases were systematically searched for articles published between 2008 and 2019 which evaluated childhood vaccination apps. Two authors screened and selected studies according to the inclusion and exclusion criteria. Data were extracted and analysed and the studies were assessed for risk of bias. Results: Twenty-eight studies evaluating 25 applications met the inclusion criteria and were included in this analysis. Nine studies assessed vaccination uptake, of which four reported significant benefit (p<.001 or p=.028) of the implementation of the application. Similarly, 4/10 indicated significant (p≤.05) impact on knowledge and 4/8 on vaccination decision-making. Patient perceptions, usability and acceptability were generally positive. The quality of the included studies was found to be moderate to poor with many aspects of the methodology being unclear. Conclusions: There was little evidence to support the use of childhood vaccination apps on improving vaccination uptake, knowledge and/or decision-making. Further research is required to understand the dichotomous effects of vaccination information provision and the evaluation of these applications in larger, more robust studies. The methodology of studies must be reported more comprehensively to accurately assess the effectiveness of childhood vaccination applications and the risk of bias of studies.